Legislation and Building Laws and Their Impact on Urban Renewal (Journal of human and social sciences, 2023)
This paper aims to study the legislation and laws related to construction, such as Urban Planning Law No. (3) of 1369, its executive regulation under the decision of the General People's Committee No. (460) of 1377/2009, and the Local Governance Law No. (59) of 2012 along with its executive regulation attached to the Council of Ministers’ Decision No. (130) of 2013. The study analyzes the impact of these laws on land use, urban renewal, reconstruction, and the urban development and growth of cities in Libya, as well as their effects on the urban landscape. The paper also highlights the comprehensiveness of these laws, their occasional conflicts, and the resulting effects on the urban features of cities, while also referring to other laws related to urban renewal, such as investment laws, and attempts to identify their shortcomings despite the absence of an explicit urban renewal law as seen in other countries. Keywords: Concept of legislation and laws – Reconstruction – Urban Renewal – Law No. (3) and its Executive Regulation – Law No. (59) and its Executive Regulation
Keywords: Legislation and Laws; Reconstruction; Urban Renewal; Law No. (3); Law No. (59)